Techno-economic feasibility analysis of Renewable-fed Power-to-Power (P2P) systems for small French islands. (1st March 2022) - Shahid, Zaib; Santarelli, M.; Marocco, P.; Ferrero, D.; Zahid, Umer
Highlights: Techno-economic analysis of RES fed H2 -Battery energy storage systems is presented. 21 French Islands (15 in Atlantic Ocean and 6 in Mediterranean Sea) are analyzed. Particle swarm optimization method for RES-P2P system sizing is implemented. Hybrid storage provides smoother process execution and long-term storage capacity. The reduction in greenhouse gases (GHGs) emissions are also investigated. Abstract: In this paper, the feasibility analysis of H2 and Battery based Power-to-Power (P2P) systems are presented from a techno-economic perspective. For this study, 21 small islands of France based in Europe are selected, being naturally endowed with renewable energy sources (RES) of solar and wind. For each island, three distinct energy storage options, i.e., hydrogen storage, battery storage and hydrogen + battery combined storage are discussed and explored. Optimum sizing of RES and P2P systems are achieved through employing particle swarm optimization (PSO) algorithm, keeping Levelized Cost of Energy (LCOE) as an objective function. The hydrogen and battery storage combination with an average LCOE value of 420Euro/MWh was found to be the most suitable option for all 21 reference islands. The associated Net Present Cost (NPC) was EUR564, 388, 050 which was lower than that for the other two storage options. The hybrid storage selection necessitated installation of 41 MW of photovoltaic (PV) modules and 122MW of wind turbines at these islands. The required storage capacity comprised of 7700MWh of hydrogen and 7MWh of battery storage combined with the auxiliaries. A considerable emphasis is also laid on highlighting the annual reduction of greenhouse gases (GHGs) and other air pollutants through the adoption of the proposed RES-P2P integrated systems. The annual carbon dioxide equivalent measure (CO2, e) of all islands was computed to be around 99507.52tons. It was revealed that more than 99 thousand tons of CO2 emissions can be prevented by avoiding consumption of more than 34 million liters of diesel per year.